Limnophora riparia - Michelsen, Verner (Zenodo, 2021)
Limnophora riparia (Fallén) (Figs 10D‒F, 12D, 13B) Calliophrys riparia (Fallén); Becker 1908a: 105 (Tenerife); Becker 1908b: 195 (Madeira); Frey 1936: 132 (Tenerife). Limnophora (Calliophrys) riparia capoverdica Emden; Emden 1958: 11 (Cape Verde Is.). Syn. nov. Limnophora (Melanochelia) riparia (Fallén); Santos Abréu 1976: 101 (La Palma). Limnophora (Calliophrys) riparia (Fallén); Hennig 1960: 391, text fig. 70C, plate figs 189, 281; Báez 1981: 637, pl. 1 fig. 8 (Tenerife, La Palma). Limnophora riparia (Fallén); Pont 1980: 749. Material examined. CAPE VERDE ISLANDS [MZH]: São Nicolau: Chã da Preguisa, 1♂, 1♀ [holotype and paratype of L. riparia capoverdica Emden, 1958] 13‒17.xii.1953 (H. Lindberg]. CANARY ISLANDS [MZH, NHMD]: TENERIFE: Icod de las Vinos, 1♂ 1931 (R. Frey). LA GOMERA: La Laja, 28°06´N 17°11´W, 480‒ 600m, 1♀ 22‒29.i.2016 (V. Michelsen). Further European material in NHMD seen from Denmark, Greece (Crete), Iceland, Spain and Sweden. Taxonomic note. Emden (1958) proposed the subspecies Limnophora (Calliophrys) riparia capoverdica for the Cape Verde population of the widespread Palearctic L. riparia , based on some differences in colour of the head and mesonotum and length of the aristal branches. On direct comparison of type specimens (see above) with specimens from the Canary Islands and various European countries I found that the colour falls within the variation of the nominal species and that the difference pertaining to the arista is non-existing. Therefore, Limnophora (Calliophrys) riparia capoverdica Emden is here considered as a synonym of Limnophora riparia (Fallén), syn. nov. Diagnosis. Small to medium sized, wing length 3.8‒5.5mm. Male: Arista short-pubescent, longest branches not quite as long greatest width of arista. Frons broad, flat, near horizontal, widening towards lunule; vertex and fronto-orbital plates in dorsal view greyish brown pruinose, long frontal triangle silvery white pruinose, frontal vitta matt black. Parafacial plates silvery white with a black patch on vibrissal area. Fronto-orbital plate with 2 orbital and 3 frontal setae. Frons lying behind moderately produced facial margin. Mesonotum light grey pruinose with three broad, dark brown stripes that occasionally merge behind the suture and dark patches at laterobasal corners of scutellum. Dorsocentral setae 4 behind the suture; presutural acrostichal field bare except for two close-set rows of setulae. Calypteres dirty whitish, wing membrane brownish tinged; vein R 4+5 on basal half between radial node and crossvein r‒m with 3‒4 dorsal setulae. Mid femur with (1‒)2 subapical pd setae and a few pv setae on basal third; mid tibia with 1 pd seta near middle. Hind femur with 3‒5 av setae on distal half, without pv setae. Sternite I bare. Sternite V and hypopygium as in Figs 10D‒F. Female: Overall larger but otherwise very similar to the male even in respect to the head characteristics. Ovipositor (Figs 12D, 13B) most similar to those of L. bipunctata and L. nitidithorax , but the lateral seta on tergite VIII is accompanied by 1‒3 fine setulae. See Table 1 for more ovipositor characters. Distribution. Cape Verde Is.: São Nicolau; Canary Islands: Tenerife, La Gomera and La Palma; Madeira. A widespread Palearctic species ranging west‒east from Macaronesia to Tajikistan. : Published as part of Michelsen, Verner, 2021, Macaronesian Muscidae (Diptera). II. The genus Limnophora Robineau-Desvoidy with description of a new Canarian endemic species, pp. 101-127 in Zootaxa 4952 (1) on page 118, DOI: 10.11646/zootaxa.4952.1.6, http://zenodo.org/record/4671806 : {"references": ["Becker, T. (1908 a) Dipteren der Kanarischen Inseln. Mitteilungen aus dem Zoologischen Museum in Berlin, 4, 1 - 180, 4 pls.", "Becker, T. (1908 b) Dipteren der Insel Madeira. Mitteilungen aus dem Zoologischen Museum in Berlin, 4,181 - 206. https: // doi. org / 10.5962 / bhl. title. 9273", "Frey, R. (1936) Die Dipterenfauna der Kanarischen Inseln und ihre Probleme. Commentationes biologicae, 6, 1 - 237, 10 pls.", "Emden, F. I. van (1958) Muscidae collected on the Cape Verde Islands. Results of the Zoological Expedition of Professor Dr. Hakan Lindberg to the Cape Verde Islands in the winter 1953 - 54. No 24. Commentationes biologicae, 20, 1 - 18.", "Santos Abreu, E. (1976) Monografia de los Anthomyidos de las Islas Canarias (Dipteros). Excmo. Cabildo Insular de La Palma, La Palma, 175 pp. [Posthumous, unedited pre- 1937 contribution.]", "Baez, M. (1981) Dipteros de Canarias VIII: Tribus Limnophorini y Coenosiini (Dipt., Muscidae). Anuario de Estudios Canaricos, 27, 619 - 670.", "Pont, A. C. (1980) Family Muscidae. In: Crosskey, R. W. (Ed.), Catalogue of the Diptera of the Afrotropical Region. British Museum (Natural History), London, pp. 721 - 761."]}